Multiscale Simulation Approach for Battery Production Systems - Schönemann, Malte; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Addressing the challenge of improving battery quality while reducing high costs and environmental impacts of the production, this book presents a multiscale simulation approach for battery production systems along with a software environment and an application procedure. Battery systems are among the most important technologies of the 21st century since they are enablers for the market success of electric vehicles and stationary energy storage solutions. However, the performance of batteries so far has limited possible applications. Addressing this challenge requires an interdisciplinary understanding of dynamic cause-effect relationships between processes, equipment, materials, and environmental conditions. The approach in this book supports the integrated evaluation of improvement measures and is usable for different planning horizons. It is applied to an exemplary battery cell production and module assembly in order to demonstrate the effectiveness and potential benefits of the simulation.
Introduction -- Battery production and simulation -- State of research for multiscale simulation of production systems -- Multiscale simulation modeling concept for battery production systems -- Implementation of a multiscale core model -- Exemplary application -- Summary and outlook.
Keywords: Renewable energy sources; Manufactures; Technological innovations; Renewable Energy; Machines, Tools, Processes; Innovation and Technology Management